Islamic Family Finance: An In-Depth Analysis of Financial Management Practices - Inayah Swasti Ratih; Zainur Ridho (Indonesian Journal of Education and Social Studies, 2022)
This research contains to assess Islamic Family Financial Management for PNM Mekaar Syariah consumers group in Jambesari District, Bondowoso. This study aims to analyze Islamic Family Financial Management for PNM Meekar Syariah customers. The research method uses descriptive research qualitative approach. Research using descriptive methods is research directed to provide symptoms, facts accurately and systematically regarding the nature of the population of a particular area. The results showed that the understanding of customers in managing household finances is very simple. Customers have budgeting and implement simple financial management. Obstacles in its implementation are due to uncertain income and low financial literacy. However, research shows that the financial management of the three households studied is mostly in accordance with the concept of Sakinah finance.